Perlindungan Hukum Terhadap Inovasi Disruptif dalam Era Digital - Priagung Pambudhi, Farrel Anhar (Jurnal Hukum Positum, 2025)
As time goes by, human knowledge also develops. Nowadays, science and technology are developing very rapidly. Today's technology impacts every area of life, including education, law, health, and the business world. The phenomenon of disruptive innovation has given rise to various types of innovation in the field of technology. The development of digital technology, which is characterized by the widespread internet network, makes it easier for people to share information. Digital disruption refers to the emergence of technological sophistication that has a significant impact on all aspects of human life. Digital transformation allows the media to combine all types and formats of information dissemination into one medium. The world is in our hands because gadgets have become magical devices that change people's information consumption habits. Innovation is actually destructive or creative, so something always gets lost, fades away and dies. All this is both frightening and over-fortifying. Trademark regulation in Indonesia began with Law Number 21 of 1961, then amended by Law Number 12 of 1992, then Law Number 15 of 2001 on Trademarks, and finally Law Number 20 of 2016 on Trademarks and Geographical Indications. Trademark protection only applies to registered trademarks. Registering a trademark provides greater protection, especially when competing with other trademarks.